MR Micro-Neurography and a Segmentation Protocol Applied to Diabetic Neuropathy. (16th April 2017) - Felisaz, P. F.; Maugeri, G.; Busi, V.; Vitale, R.; Balducci, F.; Gitto, S.; Leporati, P.; Pichiecchio, A.; Baldi, M.; Calliada, F.; Chiovato, L.; Bastianello, S.
Abstract : The aim of this study was to assess with MRI morphometric ultrastructural changes in nerves affected by diabetic peripheral neuropathy (DPN). We used an MR micro-neurography imaging protocol and a semiautomated technique of tissue segmentation to visualize and measure the volume of internal nerve components, such as the epineurium and nerve fascicles. The tibial nerves of 16 patients affected by DPN and of 15 healthy volunteers were imaged. Nerves volume (NV), fascicles volume (FV), fascicles to nerve ratio (FNR), and nerves cross-sectional areas (CSA) were obtained. In patients with DPN the NV was increased and the FNR was decreased, as a result of an increase of the epineurium (FNR in diabetic neuropathy 0, 665; in controls 0, 699, p = 0, 040 ). CSA was increased in subjects with DPN (12, 84 mm 2 versus 10, 22 mm 2, p = 0, 003 ). The FV was increased in patients with moderate to severe DPN. We have demonstrated structural changes occurring in nerves affected by DPN, which otherwise are assessable only with an invasive biopsy. MR micro-neurography appears to be suitable for the study of microscopic changes in tibial nerves of diabetic patients.